A Titanium Nitride Nanozyme for pH‐Responsive and Irradiation‐Enhanced Cascade‐Catalytic Tumor Therapy. (16th September 2021) - Liu, Jiaming; Wang, Aizhu; Liu, Shihui; Yang, Ruiqi; Wang, Longwei; Gao, Fene; Zhou, Huige; Yu, Xin; Liu, Jing; Chen, Chunying
Abstract: Nanozyme‐based catalytic tumor therapy is an emerging therapeutic method with high reactivity in response to tumor microenvironments (TMEs). To overcome the current limitations of deficient catalytic activity of nanozymes, we studied the contributing factors of enzymatic activity based on non‐metallic‐atom doping and irradiation. Nitrogen doping significantly enhanced the peroxidase activity of Ti‐based nanozymes, which was shown experimentally and theoretically. Based on the excellent NIR‐adsorption‐induced surface plasmon resonance and photothermal effect, the enzymatic activity of TiN nanoparticles (NPs) was further improved under NIR laser irradiation. Hence, an acidic TME‐responsive and irradiation‐mediated cascade nanocatalyst (TLGp) is presented by using TiN‐NP‐encapsulated liposomes linked with pH‐responsive PEG‐modified glucose oxidase (GOx). The integration of pH‐responsive GOx‐mediated H2 O2 self‐supply, nitrogen‐doping, and irradiation‐enhanced enzymatic activity of TiN NPs and mild‐photothermal therapy enables an effective tumor inhibition by TLGp with minimal side effects in vivo. Abstract : N‐doping significantly improves the peroxidase (POD) activity of titanium‐based nanozymes. Titanium nitride nanoparticles (TiN NPs) showed enhanced POD activity under NIR laser irradiation due to surface plasmon resonance (SPR) and temperature effects. Combined with glucose oxidase in liposomes, a TiN‐NP‐based nanoplatform (TLGp) showed an excellent antitumor activity under NIR‐mediated mild thermal conditions through its cascade‐catalytic activity.